Clinical gait analysis and physical examination don't correlate with physical activity of children with cerebral palsy. Cross-sectional study. Issue 1 (1st January 2020) - Guinet, Anne-Laure; Néjib, Khouri; Eric, Desailly
ABSTRACT: Gait analysis and physical clinical measures are usually performed in children with cerebral palsy to help the surgeons make therapeutic decision. However, the level of physical activity in daily life is not systematically assessed. The aim of this cross sectional study was to examine the correlations between: three-dimensional gait analysis kinematic and spatiotemporal parameters, clinical measures and physical activity. Participants were 30 children with cerebral palsy (10–18 y), with GMFCS I–III. Daily physical activity was measured with an Actigraph GT3X accelerometer in free living environment during seven consecutive days. The percent of time spent in sedentary, in moderate to vigorous physical activity and the number of steps per day were computed from the accelerometer data. Kinematics parameters did not correlate with physical activity. Moderate correlations were found between spatio-temporal parameters and physical activity, for instance timing of toe-off (r = −0.40, p = 0.03). Few physical examination parameters were correlated with physical activity, such as the hip flexors selective motor control (r = 0.69 with moderate to vigorous activity and r = 0.70 with steps per day, p < 0.05). The physical activity profile cannot be sufficiently determined by a combination of clinical measures.